Oral impalement injuries in children - Ismail, Ahmad Faisal (2019)
Impalement injuries of the oropharynx are not uncommon in children. Young children, particularly less than 5 years of age, are most involved in these types of injuries. Although most of these injuries can be managed in an outpatient setting with uneventful healing and minimal scarring, some may develop rare, critical complications. In this lecture, Dr Faisal will revisit the management protocol for oral impalement injuries in children and share his experience in the management of the cases.